1999
DOI: 10.1097/00007691-199906000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Lower Plasma Levels of Haloperidol in Smoking Than in Nonsmoking Schizophrenic Patients

Abstract: The impact of smoking on plasma haloperidol (HAL) concentrations was investigated in 66 Japanese male schizophrenic inpatients treated orally with HAL. The subjects consisted of 22 nonsmokers and 44 smokers each smoking ten cigarettes per day. Plasma concentrations of HAL were determined by an enzyme immunoassay method. There were significant positive correlations between the plasma HAL concentration and the daily dose of HAL per kg body weight (Y = 58.1X-0.01 (r = 0.86)). Smokers had significantly lower HAL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 18 publications
2
17
1
Order By: Relevance
“…A significant reduction (20-40% lower) in plasma levels is documented for clozapine (Seppala et al 1999), haloperidol (Shimoda et al 1999) and olanzapine (Zyprexa, package insert).…”
Section: Cigarette Smoking As a Possible Alleviation Of Cognitive Defmentioning
confidence: 99%
“…A significant reduction (20-40% lower) in plasma levels is documented for clozapine (Seppala et al 1999), haloperidol (Shimoda et al 1999) and olanzapine (Zyprexa, package insert).…”
Section: Cigarette Smoking As a Possible Alleviation Of Cognitive Defmentioning
confidence: 99%
“…The plasma concentration of most typical antipsychotics is significantly reduced by smoking, [36][37][38][39][40][41] an established inducer of CYP1A2. 42 Conversely, the cessation of smoking was reported to increase chlorpromazine plasma concentration and adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The authors pointed out that the CYP1A2 enzyme constitutes 12% of the total hepatic CYP content, which is an approximately sixfold greater amount than that of CYP2D6 [Shimada et al, 1994] and thus can be considered an important metabolic clearance pathway within the disposition of antipsychotics. Moreover, Basile et al [2000] stress the fact that smoking, which has been reported to induce CYP1A2 activity [Kalow and Tang, 1991], signiÂźcantly reduces the plasma concentration of most typical antipsychotics [Pantuck et al, 1982;Stimmel and Falloon, 1983;Ereshefsky et al, 1985;Jann et al, 1986;Miller et al, 1990;Shimoda et al, 1999]. Taking into consideration that a vast majority of patients suffering from schizophrenia are smokers [Hughes et al, 1986;Lohr and Flynn, 1992], Basile et al [2000] hypothesize that schizophrenic patients are likely to have both increased CYP1A2 activity and elevated CYP1A2-dependent disposition of typical antipsychotics.…”
mentioning
confidence: 99%